Observations and analysis of sinkhole growth and healing along a novel dune-based living shoreline in a swell dominated coastal application - Michael A. Angelis; Margit M.G. Maple; Maria A. Winters; Brian Leslie; Timu W. Gallien (Coastal Engineering, 2026)

Wastewater-based surveillance for Hepatitis A virus, Enterovirus, Poliovirus, and SARS-CoV-2 in São Tomé and Príncipe: A pilot study - Katia Toancha; Adjaia Borges; Lazismino Lázaro; Nilton Teixeira; Anery Katia Lima; Anabela Gonçalves; Doris Winter; Asmiralda Santos; Marcos do Nascimento; Andreza Batista de Sousa; Jürgen May; Yardlene Sacramento Sequeira; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Stress responses in pigs postweaning: Effect of heavier hybrid and weaning intact litters - Jeanet Francisca Maria Winters; Cecilie Kobek-Kjeldager; Leslie Foldager; Fernando Tecles; Lene Juul Pedersen (Applied Animal Behaviour Science, 2023)

Effects of anthropogenic pressures on the seagrass Halophila stipulacea and its associated macrozoobenthic communities in the northern Gulf of Aqaba - Hung Manh Nguyen; Cristina Andolina; Salvatrice Vizzini; Maria Cristina Gambi; Gidon Winters (Marine Environmental Research, 2023)

Equine endometrial Th1 and Th2 evaluation during early pregnancy - Gustavo R Larentis; Henrique B A Bastos; Giovani C Camozzato; Maria N Martinez; Luiz A M Centeno; Verônica L C Bueno; Gustavo H Z Winter; Sandra Fiala-Rechsteiner; Rodrigo C Mattos (Journal of Equine Veterinary Science, 2023)

Local management and landscape composition affect predatory mites in European wine-growing regions - Stefan Möth; Sylvie Richart-Cervera; Maria Comsa; Rafael Alcalá Herrera; Christoph Hoffmann; Sebastian Kolb; Daniela Popescu; Jo Marie Reiff; Adrien Rusch; Pauline Tolle; Andreas Walzer; Silvia Winter (Agriculture, Ecosystems & Environment, 2023)

Multisite assessment of the impact of a prenatal testing educational App on patient knowledge and preparedness for prenatal testing decision making - Patricia Winters; Kirsten J. Curnow; Alexandra Benachi; Maria Mar Gil; Belen Santacruz; Miyuki Nishiyama; Fuyuki Hasegawa; Haruhiko Sago (Journal of Community Genetics, 2022)
In this study, we wanted to assess the impact of the use of a patient educational app on patient knowledge about noninvasive prenatal testing (NIPT) and preparedness for prenatal screening decision-making. A randomized control study was carried out at three international sites between January 2019 and October 2020. Study participants completed a pre-consultation survey and post-consultation survey to assess knowledge, satisfaction, and preparedness for prenatal screening consultation. Providers completed a post-consultation survey. In the control arm, the pre-consultation survey was completed prior to consultation with their prenatal care provider. In the intervention arm, the pre-consultation survey was completed after using the app but prior to consultation with their prenatal care provider. Mean knowledge scores in the 203 participants using the app were significantly higher pre-consultation ( p < 0.001) and post-consultation ( p < 0.005) than those not using the app. Higher pre-consultation knowledge scores in the intervention group were observed at all sites. Most (86%) app users stated they were “Satisfied” or “Very Satisfied” with it as a tool. Providers rated the intervention group as more prepared than controls ( p = 0.027); provider assessment of knowledge was not significantly different ( p = 0.073). This study shows that clinical implementation of a patient educational app in a real-world setting was feasible, acceptable to pregnant people, and positively impacted patient knowledge.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Responses of Temperate Forests to Nitrogen Deposition: Testing the Explanatory Power of Modeled Deposition Datasets for Vegetation Gradients - Marina Roth; Hans-Gerhard Michiels; Heike Puhlmann; Carina Sucker; Maria-Barbara Winter; Markus Hauck (Ecosystems, 2021)
Eutrophication due to increased nitrogen concentrations is known to alter species composition and threaten sensitive habitat types. The contribution of atmospheric nitrogen deposition to eutrophication is often difficult to determine. Various deposition models have been developed to estimate the amount of nitrogen deposited for both entire regions and different landscape surface types. The question arises whether the resulting deposition maps allow direct conclusions about the risk of eutrophication-related changes in the understory vegetation composition and diversity in nitrogen-sensitive forest ecosystems. We combined vegetation and soil data recorded across eutrophication gradients in ten oligo-mesotrophic forest types in southwest Germany with datasets from two different deposition models specifically fitted for forests in our study region. Altogether, 153 forest stands, with three sampling replicates each, were examined. Linear mixed-effect models and NMDS analyses revealed that other site factors, in particular the soil C/N ratio, soil pH and canopy cover, played a greater role in explaining vegetation gradients than nitrogen deposition. The latter only rarely had effects on species richness (positive), nitrophyte cover (positive or negative) and the cover of sensitive character species (negative). These effects varied depending on the deposition model used and the forest types examined. No effects of nitrogen deposition on average Ellenberg N values were found. The results reflect the complex situation in forests where nitrogen availability is not only influenced by deposition but also by nitrogen mineralization and retention which depend on soil type, pH and (micro)climate. This context dependency must be regarded when evaluating the effects of nitrogen deposition.

C4 ‐dicarboxylates and l ‐aspartate utilization by Escherichia coli K‐12 in the mouse intestine: l ‐aspartate as a major substrate for fumarate respiration and as a nitrogen source - Christopher Schubert; Maria Winter; Andrea Ebert‐Jung; Sylwia Kierszniowska; Kerstin Nagel‐Wolfrum; Thorben Schramm; Hannes Link; Sebastian Winter; Gottfried Unden (Environmental Microbiology, 2021)
Summary C4‐dicarboxylates, such as fumarate, l ‐malate and l ‐aspartate represent substrates for anaerobic growth of Escherichia coli by fumarate respiration. Here, we determined whether C4‐dicarboxylate metabolism, as well as fumarate respiration, contribute to colonization of the mammalian intestinal tract. Metabolite profiling revealed that the murine small intestine contained high and low levels of l ‐aspartate and l ‐malate respectively, whereas fumarate was nearly absent. Under laboratory conditions, addition of C4‐dicarboxylate at concentrations corresponding to the levels of the C4‐dicarboxylates in the small intestine (2.6 mmol kg −1 dry weight) induced the dcuBp‐lacZ reporter gene (67% of maximal) in a DcuS‐DcuR‐dependent manner. In addition to its role as a precursor for fumarate respiration, l ‐aspartate was able to supply all the nitrogen required for anaerobically growing E . coli . DcuS‐DcuR‐dependent genes were transcribed in the murine intestine, and mutants with defective anaerobic C4‐dicarboxylate metabolism ( dcuSR , frdA , dcuB , dcuA and aspA genes) were impaired for colonizing the murine gut. We conclude that l ‐aspartate plays an important role in providing fumarate for fumarate respiration and supplying nitrogen for E . coli in the mouse intestine.

Observations and Preliminary Vulnerability Assessment of a Hybrid Dune-Based Living Shoreline - Maria A. Winters; Brian Leslie; Evyan Borgnis Sloane; Timu W. Gallien (Journal of Marine Science and Engineering, 2020)
A novel hybrid (e.g., vegetation, sand, cobble, rip-rap) nature-based dune structure was constructed at Cardiff State Beach in Encinitas, California, to protect a critical transportation artery from undermining and frequent flooding. A collaboration between regulators, funders, state agencies, professional practice and academia developed a high resolution robust unmanned aerial vehicle (UAV) based monitoring strategy to observe dune construction and evolution. Fifteen construction surveys were conducted to observe each substrate element for future morphodynamic modeling efforts. Six post-construction surveys were conducted to observe seasonal and storm-by-storm dune evolution. Backshore vulnerability was assessed using a sixty-one year time series of tides and hindcast wave forcing fit to a general extreme value distribution. The dune crest is above calculated 100-year water levels; however, the dune remains vulnerable to mass wasting caused by swash interaction at the toe of the dune. Sea-level rise will substantially increase the probability of dune erosion, breaching, and overtopping.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

First Report of CR1 Polymorphisms and Soluble CR1 Levels Associated with Late Onset Alzheimer’s Disease (LOAD) in Latin America - Gabriela Canalli Kretzschmar; Angela Adriane Hanel Antoniazzi; Luana Caroline Oliveira; Renato Mitsunori Nisihara; Maria Luiza Petzl-Erler; Ricardo Lehtonen R. de Souza; Angelica Beate Winter Boldt (Journal of Molecular Neuroscience, 2020)

Similar factors underlie tree abundance in forests in native and alien ranges - Masha T. van der Sande; Helge Bruelheide; Wayne Dawson; Jürgen Dengler; Franz Essl; Richard Field; Sylvia Haider; Mark van Kleunen; Holger Kreft; Joern Pagel; Jan Pergl; Oliver Purschke; et al. (Global Ecology and Biogeography, 2020)
Aim Alien plant species can cause severe ecological and economic problems, and therefore attract a lot of research interest in biogeography and related fields. To identify potential future invasive species, we need to better understand the mechanisms underlying the abundances of invasive tree species in their new ranges, and whether these mechanisms differ between their native and alien ranges. Here, we test two hypotheses: that greater relative abundance is promoted by (a) functional difference from locally co‐occurring trees, and (b) higher values than locally co‐occurring trees for traits linked to competitive ability. Location Global. Time period Recent. Major taxa studied Trees. Methods We combined three global plant databases: sPlot vegetation‐plot database, TRY plant trait database and Global Naturalized Alien Flora (GloNAF) database. We used a hierarchical Bayesian linear regression model to assess the factors associated with variation in local abundance, and how these relationships vary between native and alien ranges and depend on species’ traits. Results In both ranges, species reach highest abundance if they are functionally similar to co‐occurring species, yet are taller and have higher seed mass and wood density than co‐occurring species. Main conclusions Our results suggest that light limitation leads to strong environmental and biotic filtering, and that it is advantageous to be taller and have denser wood. The striking similarities in abundance between native and alien ranges imply that information from tree species’ native ranges can be used to predict in which habitats introduced species may become dominant.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Towards a macroscope: Leveraging technology to transform the breadth, scale and resolution of macroecological data - Maria Dornelas; Elizabeth M. P. Madin; Michael Bunce; Joseph D. DiBattista; Mark Johnson; Joshua S. Madin; Anne E. Magurran; Brian J. McGill; Nathalie Pettorelli; Oscar Pizarro; Stefan B. Williams; Marten Winter; et al. (Global Ecology and Biogeography, 2019)
The problem Earth‐based observations of the biosphere are spatially biased in ways that can limit our ability to detect macroecological patterns and changes in biodiversity. To resolve this problem, we need to supplement the ad hoc data currently collected with planned biodiversity monitoring, in order to approximate global stratified random sampling of the planet. We call this all‐encompassing observational system ‘the macroscope’. The solution With a focus on the marine realm, we identify seven main biosphere observation tools that compose the macroscope: satellites, drones, camera traps, passive acoustic samplers, biologgers, environmental DNA and human observations. By deploying a nested array of these tools that fills current gaps in monitoring, we can achieve a macroscope fit for purpose and turn these existing powerful tools into more than the sum of their parts. An appeal Building a macroscope requires commitment from many fields, together with coordinated actions to attract the level of funding required for such a venture. We call on macroecologists to become advocates for the macroscope and to engage with existing global observation networks.

Inhibition of Semaphorin3A Promotes Ocular Dominance Plasticity in the Adult Rat Visual Cortex - Elena Maria Boggio; Erich M. Ehlert; Leonardo Lupori; Elizabeth B. Moloney; Fred De Winter; Craig W. Vander Kooi; Laura Baroncelli; Vasilis Mecollari; Bas Blits; James W. Fawcett; Joost Verhaagen; Tommaso Pizzorusso (Molecular Neurobiology, 2019)

Tall-statured grasses: a useful functional group for invasion science - Susan Canavan; Laura A. Meyerson; Jasmin G. Packer; Petr Pyšek; Noëlie Maurel; Vanessa Lozano; David M. Richardson; Giuseppe Brundu; Kim Canavan; Angela Cicatelli; Jan Čuda; Wayne Dawson; et al. (Biological Invasions, 2019)

On the structural and species diversity effects of bark beetle disturbance in forests during initial and advanced early-seral stages at different scales - Maria-Barbara Winter; Claus Bässler; Markus Bernhardt-Römermann; Franz-Sebastian Krah; Hanno Schaefer; Sebastian Seibold; Jörg Müller (European Journal of Forest Research, 2017)

Environmental impact of traction electric motors for electric vehicles applications - Maria Hernandez; Maarten Messagie; Omar Hegazy; Luca Marengo; Oliver Winter; Joeri Van Mierlo (The International Journal of Life Cycle Assessment, 2017)

Modeling the Disease Progression from Healthy to Overt Diabetes in ZDSD Rats - Steve Choy; Willem de Winter; Mats O Karlsson; Maria C Kjellsson (The AAPS Journal, 2016)

The effects of CO2 and nutrient fertilisation on the growth and temperature response of the mangrove Avicennia germinans - Ruth Reef; Martijn Slot; Uzi Motro; Michal Motro; Yoav Motro; Maria F. Adame; Milton Garcia; Jorge Aranda; Catherine E. Lovelock; Klaus Winter (Photosynthesis Research, 2016)

Regeneration dynamics and resilience of unmanaged mountain forests in the Northern Limestone Alps following bark beetle-induced spruce dieback - Maria-Barbara Winter; Roland Baier; Christian Ammer (European Journal of Forest Research, 2015)

The impact of Natura 2000 on forest management: a socio-ecological analysis in the continental region of the European Union - Susanne Winter; Lars Borrass; Maria Geitzenauer; Marieke Blondet; Ruth Breibeck; Gerhard Weiss; Georg Winkel (Biodiversity and Conservation, 2014)

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Plectin–intermediate filament partnership in skin, skeletal muscle, and peripheral nerve - Maria J. Castañón; Gernot Walko; Lilli Winter; Gerhard Wiche (Histochemistry and Cell Biology, 2013)

The impact of climate on radial growth and nut production of Persian walnut (Juglans regia L.) in Southern Kyrgyzstan - Maria-Barbara Winter; Barbara Wolff; Hagen Gottschling; Paolo Cherubini (European Journal of Forest Research, 2009)

A simple voltammetric procedure for speciation and evaluation of As removal from water - Maria do Socorro S. Pereira; Eduardo Winter; Jose Roberto Guimarães; Susanne Rath; Anne Hélène Fostier (Environmental Chemistry Letters, 2007)

Fine mapping of the Schnyder?s crystalline corneal dystrophy locus - Veena Theendakara; Gerard Tromp; Helena Kuivaniemi; Peter S. White; Seema Panchal; Jennifer Cox; R. Scott Winters; Petra Riebeling; Frank Tost; Maria Hoeltzenbein; Timo M. Tervo; Wolfram Henn; et al. (Human Genetics, 2004)

Pinealectomy-associated decrease in ribosomal gene activity in rats - Spencer Luiz Marques Payão; Cristina Valetta de Carvalho; Edson Roberto da Silva; Cristiane Lopes; Regina Pekelmann Markus; Lucile Maria Floeter Winter; Marília de Arruda Cardoso Smith (Biogerontology, 2001)

Oto-facio-cervical (OFC) syndrome is a contiguous gene deletion syndrome involving EYA1 : molecular analysis confirms allelism with BOR syndrome and further narrows the Duane syndrome critical region to 1 cM - Sarah Rickard; William van't Hoff; Angela Barnicoat; Isabelle Russell-Eggitt; Robin Winter; Maria Bitner-Glindzicz; Michael Parker (Human Genetics, 2001)